The Quest for environmentally sustainable transport development: A comparison of 4 cities in 4 countries - Langeland, Anders (Proceedings from the Annual Transport Conference at Aalborg University, 2009)
This paper describe a study of the land use and transport planning in four cities1 that are renown and prize awarded for their sustainable development efforts: Kristiansand (Norway), Aalborg (Denmark), Norwich (England) and Davis (California, USA). The four cities were compared cross borders and lessons were drawn. The focus of the project has been to explore how land use and transport planning have been used to achieve environmentally sustainable transport (EST)2 in cities: “Transportation that does not endanger public health or ecosystems and meets mobility needs consistent with • use of renewable resources at below their rates of regeneration • use of non-renewable resources at below the rates of development of renewable substitutes.” The research question asked was: How can land use and transport planning be used to create / increase environmentally sustainable transport in cities, what are the barriers for sustainable transport development and what promotes such development? The project aimed at answering these questions: How was the connection and interaction between land use and transport in the cities? What effect did planning and policy exert on the choice of transport mode? Was the development caused by a deliberate policy and was it sustainable, and in case how and why How could the observed land use and transport development be explained? What were the factors facilitating cycling, walking and public transport; and what were the factors inhibiting more sustainable transport development? What if any, are the lessons from the case cities for other medium sized cities in Europe?